2014
DOI: 10.5657/kfas.2014.0508
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Antimicrobial Resistance of Vibrio parahaemolyticus Isolated from Korean Shellfish

Abstract: The contamination status of Vibrio parahaemolyticus in commercially valuable shellfish from the south and west coasts of Korea and the antimicrobial resistance patterns of isolated V. parahaemolyticus were investigated from July through October, 2011. The range of V. parahaemolyticus concentrations in oysters Crassostrea gigas and short neck clams Venerupis philippinarum was <30~290 MPN/100 g and <30~46,000 MPN/100 g, respectively, and greater than 10,000 MPN/100 g of V. parahaemolyticus was detected from 7 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Yu et al . () showed 43·6% of V. parahaemolyticus isolated from shellfish were resistant to AMP, but all isolates were tdh or trh ‐negative. Lee et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yu et al . () showed 43·6% of V. parahaemolyticus isolated from shellfish were resistant to AMP, but all isolates were tdh or trh ‐negative. Lee et al .…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al . () reported that none of the 436 isolates from shellfish farm was tdh or trh ‐positive. Park et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…oxytetracycline, tetracycline, quinolone, sulphonamides trimethoprim , , (Oh et al, 2011;Rico et al, 2012;Sani et al, 2013;Xu et al, 2014;Yano et al, 2014;Yu et al, 2014). (Okamoto et al, 2009;Letchumanan et al, 2015).…”
Section: Pcrmentioning
confidence: 99%